2020
DOI: 10.1038/s41598-020-79303-0
|View full text |Cite
|
Sign up to set email alerts
|

A simple method using CRISPR-Cas9 to knock-out genes in murine cancerous cell lines

Abstract: CRISPR-Cas9 system can be used to generate knock-out cancer cell lines. An insertion or deletion induced by a single guide RNA (gRNA) is often used to generate knock-out cells, however, some cells express the target gene by skipping the disrupted exon, or by using a splicing variant, thus losing the target exon. To overcome this unexpected expression of the target gene, almost the entire gene can be swapped with a selection marker. However, it is time-consuming to create a targeting vector which contains 5′ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Since the emergence of knockout strategies, they have been the most commonly and widely used method for establishing an understanding of human pathogens. The emergence of more efficient knockout generation technologies, like CRISPR, has contributed considerably to the genetic engineering of pathogens [ 67 ]. C. albicans was among the first human pathogens in which the GlcNAc metabolic pathway was thoroughly studied, and Bhattacharya et al [ 68 ] first reported that the presence of GlcNAc is essential for the induction of GlcNAc kinase.…”
Section: Engineering Glcnac Catabolic Pathway For Reducing the Virule...mentioning
confidence: 99%
“…Since the emergence of knockout strategies, they have been the most commonly and widely used method for establishing an understanding of human pathogens. The emergence of more efficient knockout generation technologies, like CRISPR, has contributed considerably to the genetic engineering of pathogens [ 67 ]. C. albicans was among the first human pathogens in which the GlcNAc metabolic pathway was thoroughly studied, and Bhattacharya et al [ 68 ] first reported that the presence of GlcNAc is essential for the induction of GlcNAc kinase.…”
Section: Engineering Glcnac Catabolic Pathway For Reducing the Virule...mentioning
confidence: 99%
“…Additionally, the PCR experiment with PSCs 10 days post-transfection does not reveal any detectable amplicon of transgene Cas9 (Figure 3). The most laborious step in viral delivery is to expand mutant cell pools into single clones (e.g., 96-well plate), which, depending on protocols, requires additional 2-3 weeks or more (Lino et al, 2018;Giuliano et al, 2019;Ishibashi et al, 2020;Lu et al, 2020). Some protocols also require both puromycin-and FACS-based selection, although this technique is praiseworthy since only cells with the highest transduction efficiency are selected (Lino et al, 2018;Giuliano et al, 2019;Ishibashi et al, 2020;Lu et al, 2020), yet these require sophisticated lab setup with flow cytometry and expertise, and are also very time-consuming and laborious.…”
Section: Resultsmentioning
confidence: 99%
“…For RNAseq analysis of HL60 cells, we compared akirin2 KO with WT cells as previously shown in CRISPR-Cas9 experiments (i.e. [30]) (Supplementary Data S2). RNA was isolated from WT and akirin2 KO HL60 cells (three Upper plots show the thermogram and lower plots show the interaction isotherm.…”
Section: Rnaseq Transcriptomics Data Acquisition and Analysis In Human Hl60 Cellsmentioning
confidence: 99%